Tips to manage weed seed bank under Conservation Agriculture-based farming systems in drylands - Devkota Wasti, Mina Kumari; Haddad, Atef; Moussadek, Rachid; M'hamed, Hatem Cheikh; Khalil, Yaseen (International Center for Agricultural Research in the Dry Areas, 2023)
Weed management in the drylands is complex because of heterogeneous soil conditions, increasing frequency of extreme events (drought, torrential rainfall, and extreme temperatures), a wide range of environmental requirements of botanically diverse weed species, and limited farmers’ resources. Weeds can survive under adverse conditions, as they extract more water and nutrients from the soil, thereby reducing crop yield by 37 to 79% in dryland agriculture. Weeds are the most detrimental factor in decreasing the water availability to growing crops in dryland, where weeds alone can reduce more than 50% of crop yield competition for moisture in moisture-limited conditions. The severity of weed infestation and its management during the transition phase from conventional agriculture to Conservation Agriculture (CA), is one of the bottlenecks for wider adoption of CA in the Middle East and North Africa (MENA) region. More aggressive, adaptive, and persistent characteristics of weeds pose a serious threat to crop production and are difficult to control below the economic threshold level with single weed management practice. Managing weed seed banks is an important component of integrated weed management for CA.